أثر الثقافة التنظيمية على المشاركة في صنع القرار ((دراسة حالة الشركة العامة لمصفاة بانياس)) - ديوب, محمد; جمعه, رماح (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدف البحث إلى التعرف على دور الثقافة التنظيمية في المشاركة في صنع القرار في الشركة العامة لمصفاة بانياس. وقد اعتمد البحث ثلاث عناصر للثقافة التنظيمية هي التعاون والتماسك والفاعلية أما المشاركة في صنع القرار فقد حدد بثلاث عناصر هي الاعتقاد بفاعلية المشاركة وإدراك أثر المشاركة على قوة المدير والالتزام بالمشاركة. وجمعت البيانات عن طريق استبانة صممت لهذا الغرض ووزعت على عينة مكونة من ((40))من العاملين في الشركة العامة لمصفاة بانياس . ولاختبار فرضيات البحث تم استخدام معامل التباين الأحادي وتوصل البحث إلى مجموعة نتائج أبرزها:ارتفاع مستوى التطبيق لعناصر الثقافة التنظيمية وعناصر المشاركة في صنع القرار في الشركة العامة لمصفاة بانياس.وجود فروق ذات دلالة إحصائية لجميع عناصر المشاركة في صنع القرار تعزى لعناصر الثقافة التنظيمية.وقدم البحث مجموعة توصيات أبرزها ضرورة تفويض السلطة والاهتمام بمقترحات العاملين وعدم إهمالها من قبل المديرين.The searching to the acquaintance on regulatory role the culture in the participation in decision-making in the company aimed the common people of the colander baanyaas. The searching depended three elements for the culture regulatory she the cooperation and the adherence and the efficiency as for associated in decision-making losing determined in three elements she the associated belief in efficiency and apprehension of favored associated on strength of the manager and the observance in the participation. Inclusion of the searching theoretical offers about concepts of the culture regulatory and the participation in decision-making and week of the statements about road of showing become deaf consequently the purpose and formative sample distributed on from ((40))From working in the company the common people of the colander baanyaas. For test the hypothetical searching use treated of the mono discrepancy and her was complete produced continuity of the searching to Group the results:ـ rise level of the application the regulatory elements the culture and associated elements in decision-making in the company the common people of the colander baanyaas.- presence differences self of evidence of statistical the all associated elements in decision-making becomes strong the regulatory elements the culture. Foot of the searching her group recommendations of produced necessity authorization of the authority and the interest in proposed working and her lack of negligence before the managers.